"Coniugalia praecepta" Plutarcha o życiu żon - Budzanowska-Weglenda, Dominika (Vox Patrum, 2016)
The good wife, as Plutrach taught, ought to have no feeling of her own, but she should join with her husband in seriousness and sportiveness, in soberness and laughter. The husband has to be pure and clean from all connexion with others when he approach his wife and her virtue, her exclusive devotion to her husband, her constancy, and her affection, ought to be most in evidence. The man ought to exercise control over the woman, not as the owner has control over a piece of property, but, as the soul colonists the body, by entering into her feelings and being knit to her through goodwill. He is teacher of philosophy, she is his disciple: for his wife husband must collect from every source what is useful and carrying it within his own self impart it to her, and then discusses it with her, and makes the best of these doctrines her favourite and familiar themes.